Comparative Study of High Performance Polymers in Selective Inhibition Sintering Process through Finite Element Analysis. Issue 3 (March 2017) - Aravind, A.; Siddiqui, T.N.; Arunkumar, P.; Balasubramanian, E.
Selective Inhibition Sintering (SIS) is a novel additive manufacturing process which uses indigenously available polymers and the high cost laser system is avoided that makes the system cost-effective. Finite Element Analysis (FEA) is carried out to evaluate the performance of SIS process. The effect of temperature on the polymer structure is examined through coupled field transient thermo-structural analysis of various high performance polymer particles such as Polysulfone (PSU), Polybenzimidazole (PBI), Polyimide (PI), Polyethersulfone (PES), Perfluoroalkoxy alkanes (PFA), Ethylene tetrafluoroethylene (ETFE) and KCl is used as the inhibitor material. The structured finite element mesh model is created and heat flux is applied in equivalent time intervals to study the transient characteristics. Simulation results are presented with displacement, temperature and thermal stress for each polymer materials and their characteristics performance is evaluated.